Characterization of PCFC‐Electrolytes Deposited by Reactive Magnetron Sputtering; Comparison with Ceramic Bulk Samples1. Issue 4 (8th May 2013) - Arab Pour Yazdi, M.; Briois, P.; Georges, S.; Costa, R.; Billard, A.
Abstract SrZr0.84Y0.16O3–α (SZY16), BaZr0.84Y0.16O3–α (BZY16), BaCe0.8Zr0.1Y0.1O3–α (BCZY10), and BaCe0.90Y0.10O3–α (BCY10) thin films with the thickness of lower than 6 micron are successfully deposited by reactive magnetron sputtering on alumina substrate covered by about 200 nm Pt3Ti collector layer. The corresponding ceramic bulk samples are prepared by solid state reaction. In order to obtain dense BZY16 and BCZY10 samples, 1 wt.% ZnO was added before sintering process. As deposited films are amorphous and crystallise under the expected crystal structure at different temperatures (e.g., SZY16 ≈ 623 K; BZY16 ≈ 423 K; BCY10 ≈ 873 K, and BCZY10 ≈ 873 K). SZY16 and BZY16 coatings are stable in air with respect to carbonation and hydration. BZY16 coatings require an in situ crystallization in order to avoid further cracking due to the tensile stress generation associated with the crystallization phenomenon, so they are deposited directly onto hot substrate (Tsubstrate ≈ 523 K). BCZY10 amorphous coatings present a good chemical stability against carbonation in air up to 573 K but the coatings decompose in BaCO3 and CeO2 mixture after annealing treatment at around 873 K for 2 h in air, instead of the expected double substituted BaCeO3 perovskite structure. Nevertheless, the crystallization perovskite structure is obtained after annealing treatment under vacuum to prevent the carbonation of the coating. BCY10 requires in situ crystallisation (Tsubstrate ≈ 873 K) to obtain BaCeO3 structure while avoiding the carbonation of the film. All the bulk samples present the perovskite structure with a relative density higher than ∼80% and without trace of ZnO or BaCO3. Eighty percent of relative density was demonstrated to give a good compromise between porosity and grain boundary blocking effects. The electrical properties of the films and pellets are investigated by AC impedance spectroscopy in air. Conductivities of crystallised coatings are close but always significantly lower than those of ceramic bulk samples of the same composition.